Dynamic Model and Vibration Power Flow of a Rigid-Flexible Coupling and Harmonic-Disturbance Exciting System for Flexible Robotic Manipulator with Elastic Joints - Yufei Liu; Wei Li; Yuqiao Wang; Xuefeng Yang; Jinyong Ju (Shock and Vibration)
This paper investigates the dynamic of a flexible robotic manipulator (FRM) which consists of rigid driving base, flexible links, and flexible joints. With considering the motion fluctuations caused by the coupling effect, such as the motor parameters and mechanism inertias, as harmonic disturbances, the system investigated in this paper remains a parametrically excited system. An elastic restraint model of the FRM with elastic joints (FRMEJ) is proposed, which considers the elastic properties of the connecting joints between the flexible arm and the driving base, as well as the harmonic disturbances aroused by the electromechanical coupling effect. As a consequence, the FRMEJ accordingly remains a flexible multibody system which conveys the effects of rigid-flexible couple and electromechanical couple. The Lagrangian function and Hamilton’s principle are used to establish the dynamic model of the FRMEJ. Based on the dynamic model proposed, the vibration power flow is introduced to show the vibration energy distribution. Numerical simulations are conducted to investigate the effect of the joint elasticities and the disturbance excitations, and the influences of the structure parameters and motion parameters on the vibration power flow are studied. The results obtained in this paper contribute to the structure design, motion optimization, and vibration control of FRMs.